Running - testing yourself - Galloway, Jeff (Meyer & Meyer Sport (UK) Ltd., 2005)
For runners and walkers who want to improve, "Running -Testing Yourself offers programs and practical tips to go farther, go faster, while enjoying exercise more than ever. Olympian Jeff Galloway offers detailed advice on how to build the length of a run or walk without injury -- and run faster.